Flexible paths to assessment for OER learners: A comparative study - Dianne Conrad; Rory McGreal (Journal of Interactive Media in Education, 2012)
This paper highlights the preliminary findings of a one-year research project (2011) that investigated the fit of recognizing prior learning (RPL) practice and related assessment and transfer protocols to projected OER use, especially by the Open Educational Resource University (OERu), a newly-formed consortium of like-minded institutions located worldwide. Across a study that included 31 post secondary institutions from 10 countries, findings indicated both consistencies and inconsistencies in the treatment of RPL. While most institutions reflected the intent of honoring learners' prior learning, achieved informally or non-formally, institutions were bound by internal policy and structure in terms of protocols. The relationship of transfer credit opportunities to engaging with learners in preparing RPL documents for assessment was also varied. Broad disparities in fee information made it difficult to determine what the actual costs of various protocols would be for learners. OERu will continue to search for innovative approaches to providing universal and collaborative education, globally, to non-traditional learners. Keywords: Open Educational Resources, OER, Open Educational Resource University, OERu, assessment, recognition of prior learning, RPL, access, credentialisation, policy